Ekofeminisme dalam Novel Perempuan Laut Karya Usman Arrumy - Arifin, Dedi; Astuti, Cutiana Windri; Setiawan, Agus (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The purpose of this study is to analyze, identify, and describe ecofeminism in the novel Perempuan Laut based on ecofeminism theory. In popular ecofeminism theory, women’s existence can be seen from three perspectives, natural ecofeminism, spiritual ecofeminism, and socialist ecofeminism. The method used in this study is descriptive qualitative. Data collection techniques are done by note-taking and document analysis, while the data analysis technique used is descriptive analysis. Based on the results of the study, it can be concluded that in the novel Perempuan Laut by Usman Arrumy there are three forms of ecofeminism, namely: (1) natural ecofeminism, including Lare’s struggle since childhood, women’s persistence, caring for the environment and the ability to produce coffee; (2) spiritual ecofeminism, including natural works and women’s works alike, and describing how she cares for the island; and (3) socialist ecofeminism, including respecting fellow human beings, maintaining skills, discrimination, and rejecting the logic of discrimination or male domination.